Effects of 12-week gait retraining on plantar flexion torque, architecture, and behavior of the medial gastrocnemius in vivo - Zhang, Chuyi; Deng, Liqin; Zhang, Xini; Wu, Kaicheng; Zhan, Jianglong; Fu, Weijie; Jin, Jing (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: This study aims to explore the effects of 12-week gait retraining (GR) on plantar flexion torque, architecture, and behavior of the medial gastrocnemius (MG) during maximal voluntary isometric contraction (MVIC). Methods: Thirty healthy male rearfoot strikers were randomly assigned to the GR group (n = 15) and the control (CON) group (n = 15). The GR group was instructed to wear minimalist shoes and run with a forefoot strike pattern for the 12-week GR (3 times per week), whereas the CON group wore their own running shoes and ran with their original foot strike pattern. Participants were required to share screenshots of running tracks each time to ensure training supervision. The architecture and behavior of MG, as well as ankle torque data, were collected before and after the intervention. The architecture of MG, including fascicle length (FL), pennation angle, and muscle thickness, was obtained by measuring muscle morphology at rest using an ultrasound device. Ankle torque data during plantar flexion MVIC were obtained using a dynamometer, from which peak torque and early rate of torque development (RTD50) were calculated. The fascicle behavior of MG was simultaneously captured using an ultrasound device to calculate fascicle shortening, fascicle rotation, and maximal fascicle shortening velocity (Vmax). Results: After 12-week GR, (1) the RTD50 increased significantly in the GR group (p = 0.038), (2) normalized FL increased significantly in the GR group (p = 0.003), and (3) Vmax increased significantly in the GR group (p = 0.018). Conclusion: Compared to running training, GR significantly enhanced the rapid strength development capacity and contraction velocity of the MG. This indicates the potential of GR as a strategy to improve muscle function and mechanical efficiency, particularly in enhancing the ability of MG to generate and transmit force as well as the rapid contraction capability. Further research is necessary to explore the effects of GR on MG behavior during running in vivo.